2020
DOI: 10.1007/s10557-020-07035-4
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Albuminuria as a Biomarker of Diabetic Complications

Abstract: Diabetes mellitus is a disease of dysregulated blood glucose homeostasis. The current pandemic of diabetes is a significant driver of patient morbidity and mortality, as well as a major challenge to healthcare systems worldwide. The global increase in the incidence of diabetes has prompted researchers to focus on the different pathogenic processes responsible for type 1 and type 2 diabetes. Similarly, increased morbidity due to diabetic complications has accelerated research to uncover pathological changes cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 126 publications
0
18
0
1
Order By: Relevance
“…Albuminuria is thought to be the result of pathogenic events targeting the vasculature, the glomerulus, and tubular cells [35][36][37]. In this study we show that FMD does not change ACR levels in the overall group, but only in patients with microalbuminuria.…”
Section: Discussionmentioning
confidence: 43%
“…Albuminuria is thought to be the result of pathogenic events targeting the vasculature, the glomerulus, and tubular cells [35][36][37]. In this study we show that FMD does not change ACR levels in the overall group, but only in patients with microalbuminuria.…”
Section: Discussionmentioning
confidence: 43%
“…15 Pappitha Raja found a positive correlation between albuminuria and dysregulation of glomerular pore size. 16 On the basis of these references, findings of our study may be explained as follows. .…”
Section: Discussionmentioning
confidence: 76%
“…Our findings suggested that urine NAG could be considered a more promising indicator for detecting the development of DN early in children with diabetes in a pre-albuminuric state than the other five renal injury markers investigated in our study. Obesity remains a strong environmental factor triggering the onset of DM, yet tighter glycemic control appears to be more critical than maintaining normal weight in order to reduce early progression to DN [ 20 ]. After exploring the characteristics of the six renal injury markers among obese and non-obese children and children with and without diabetes, we suggest that urine NAG could be a more sensitive biomarker that is closely linked to glycemic status, and thus could be considered an early indicator of future development of DN.…”
Section: Discussionmentioning
confidence: 99%